Penentuan Konsentrasi Efektif Ekstrak Tanaman Patikan Kebo (Euphorbia Hirta) Merah Dan Hijau Dalam Melarutkan Kalsium - Hamdiana, Hamdiana; Jura, Minarni Rama; Ratman, Ratman (Jurnal Akademika Kimia, 2017)
The use of traditional materials is one alternative for the treatment of kidney stones. One of them is utilizing a plant of patikan kebo (Euphorbia hirta). This study is conducted by using laboratory experiments and the extract of the plant of patikan kebo red and patikan kebo green to dissolve the calcium phosphate as a substitute for kidney stones. The extraction of samples is conducted by decoction. The aim of the study is to determine the effective concentration of the extracts of patikan kebo red and green to dissolve calcium and test the effectiveness of the extracts of patikan kebo to dissolve calcium compared to Batugin elixir and distilled water. Determination of the concentration of dissolved calcium in the extracts using a flame photometer. The results show that the extract of patikan kebo red with a concentration of 2.1% is effective in dissolve the calcium with a concentration of 5.2 ppm. The extract of patikan kebo green with a concentration of 27.4% is effective in dissolving the calcium with a concentration of 27.5 ppm. When compared with Batugin elixir and distilled water, Batugin elixir can only dissolve the calcium with concentration 15.3 ppm, while distilled water can only dissolve 3 ppm of the calcium.